De l’utopie à l’autonomadie, un autre voyage est possible ! - Franck Michel (Études Caribéennes)
Can holidays last or even go on forever? Utopia is one of the ways to think this option, to operate this step aside, against the current of the surrounding and dominant order. From Segalen to Cendrars, the test of travel and exoticism without voyeurism carries in it the proofs of the trip or the act of slinging. Autonomy and nomadism are the appropriate terms that open and sometimes force the doors of consensus, immobilism and generalized fear. These two terms - at the origin of which I named “autonomadie” (in French, quite untranslatable) - refer to independence of mind, freedom of expression and the free flow of ideas, people, long before that of goods. If the planet is the foundation of all travel, culture is its driving force. This article tries to mark new paths of travel, off the beaten track, nourished by the imagination of elsewhere, and necessarily alternative. Yesterday as today, it is always a matter of rising to better stand up, and therefore not to fall and die. Especially in this good way of a beautiful promising life that leads to oneself as to the others. Humanity is nothing without freedom of movement. It is nothing without movement and freedom. Humans are not automated subjects but autonomous nomads. And active travelers rather than passive tourists. This is what this contribution intends not to affirm but to explore.